Analysis of the frequency and degree of temporomandibular disorder in patients with head and neck cancer undergoing radiotherapy - Douglas Roberto Pegoraro; Barbara Zanchet; Caroline de Oliveira Guariente; Josemara de Paula Rocha; Juliana Secchi Batista
Abstract Introduction: Head and neck cancer is responsible for an increasing incidence of primary malignant neoplasm cases worldwide. Radiotherapy is one of the treatments of choice for this type of cancer, but it can cause adverse effects, such as temporomandibular disorder. The objective of this study was to characterize the degree and frequency of temporomandibular disorder in patients with head and neck cancer undergoing radiotherapy. Method: This research was quantitative, descriptive and exploratory. The sample consisted of 22 patients that answered assessment questions and the Helkimo anamnestic questionnaire, modified by Fonseca (1992). The data were collected from May to October 2014, and statistically analyzed using the Chi-square test, with a significance level of p ≤ 0.05. Results: Of the 22 patients, 86.4 % were male, with a mean age of 58.86 ± 9.41 years. Temporomandibular disorder was present in 31.8% of the subjects, based on the assessment prior to radiotherapy, and in 59.1% in the post-treatment assessment. Among all questions, the most frequent was "Do you use only one side of the mouth to chew?" with 22.7% "yes" answers, both at the first assessment and at the post treatment. Conclusion: According to the results of this study, temporomandibular disorder is a disease that is present with a high prevalence in people diagnosed with head and neck cancer undergoing radiotherapy.